Maritime Character Learning Traditions in the Wakatobi Communities - Rudi, La; Hanum, Farida; Wahyono, Sugeng B (Universitas Islam Negeri Raden Intan Lampung, 2024)
One of the paradigms for looking at character or personality is culture. This paradigm sees character not only influenced by culture but shaped by culture itself. This affirms that the character of society is dynamic, it will always differ depending on the cultural context that forms it. This article aims to elaborate on the tradition of character learning in maritime society. The source of the data is the result of ethnographic studies in Wakatobi Regency. Data collection was carried out by depth interviews, participant observation, and literature review. The results showed that the distinctive character of marine communities that are tough, hardworking, unyielding, honest, responsible, and friendly to nature, is not formed naturally. Nautical character is shaped by a cultural environment full of challenges and risks, however life in the sea is related to matters of life and death. There are four stages of character learning tradition in nautical society, namely: character learning through prospective sailors, chefs, mustards, and masters. The four stages are an interrelated process, which shows the importance of character building in maritime culture.